Bibliometric analysis of social entrepreneurship: trends, themes, and future directions - Azizi, Karim; Osman, Muhamad Zulkiflee; Rumangkit, Stefanus; Pratama, Yan Aditiya (Indonesia Research and Study Center, 2026)
This study aims to provide a comprehensive bibliometric analysis of social entrepreneurship (SE) literature, identifying emerging trends, key themes, and influential research clusters that have shaped its development. The research seeks to bridge the gap in existing literature by offering a systematic examination of the field's evolution, revealing research gaps, and proposing future directions. The study utilizes data sourced from the Scopus database, covering articles published between 2020 and 2025. A bibliometric approach was employed using R Studio to analyze key indicators such as publication trends, author collaborations, keyword co-occurrences, and citation performance. The analysis highlights the top 10 journals contributing to social entrepreneurship research, with the Journal of Social Entrepreneurship leading in article publications. Additionally, it identifies the countries with the highest citation counts, with the USA, UK, and India taking the lead. Co-occurrence and clustering analysis further reveal five distinct research clusters, focusing on the financial, social, and personal dimensions of social entrepreneurship, including topics like social impact, business models, sustainability, and social value creation. The study also identifies future research areas such as gender, social capital, the theory of planned behavior, and social value creation, which are critical for advancing the field. The findings contribute to a better understanding of social entrepreneurship’s trajectory and offer valuable insights for scholars, policymakers, and practitioners aiming to enhance the field’s impact and sustainability